2007
DOI: 10.1007/s00125-007-0782-1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of peroxisome proliferator-activated receptor gamma coactivator gene (PGC1A) during weight loss is related to insulin sensitivity but not to energy expenditure

Abstract: Aims/hypothesis We investigated whether skeletal muscle peroxisome proliferator-activated receptor gamma coactivator-1 (PGC1A; also known as PPARGC1A) and its target mitofusin-2 (MFN2), as well as carnitine palmitoyltransferase-1 (CPT1; also known as carnitine palmitoyltransferase 1A [liver] [CPT1A]) and uncoupling protein (UCP)3, are involved in the improvement of insulin resistance and/or in the modification of energy expenditure during surgically induced massive weight loss. Materials and methods Seventee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 42 publications
12
37
0
Order By: Relevance
“…In this study we have demonstrated that MFN2 is upregulated in skeletal muscle from morbidly obese NGT patients in response to BPD, which correlates positively with glucose oxidation. This is in keeping with previous findings observed in women subjected to BPD [18] or in patients in whom weight loss was induced by Roux-en-Y gastric bypass [32]. Our data additionally indicate that MFN2 expression is a good predictor of fasting glucose oxidation in NGT patients, much better than the expression of genes encoding for regulators of mitochondrial biogenesis such as PGC-1α or PGC-1β, and also better than the expression of genes encoding for constitutive proteins such as porin or citrate synthase (and therefore markers of mitochondrial mass).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study we have demonstrated that MFN2 is upregulated in skeletal muscle from morbidly obese NGT patients in response to BPD, which correlates positively with glucose oxidation. This is in keeping with previous findings observed in women subjected to BPD [18] or in patients in whom weight loss was induced by Roux-en-Y gastric bypass [32]. Our data additionally indicate that MFN2 expression is a good predictor of fasting glucose oxidation in NGT patients, much better than the expression of genes encoding for regulators of mitochondrial biogenesis such as PGC-1α or PGC-1β, and also better than the expression of genes encoding for constitutive proteins such as porin or citrate synthase (and therefore markers of mitochondrial mass).…”
Section: Discussionsupporting
confidence: 93%
“…Increased PGC-1α expression has also been reported in muscle from obese patients after weight loss induced by Roux-en-Y gastric bypass [32]. In contrast, PGC-1α, PGC-1β, PPAR-δ and SIRT1 were not induced in morbidly obese type 2 diabetic patients in response to BPD, which explains the lack of stimulation of genes encoding for mitochondrial proteins (citrate synthase, porin or MFN2) and the blunted changes of glucose and lipid oxidation particularly under fasting conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Insulin resistance is a phenotype of obesity and type 2 diabetes, and we (5) and others (7,10,11,20) have previously reported improved peripheral glucose disposal rates following RYGB, in both subjects with normal glucose tolerance and type 2 diabetes. One possible mediator of this improvement in insulin sensitivity is adiponectin.…”
Section: Discussionmentioning
confidence: 77%
“…However, the PPAR co-activator-1α, PGC1α, did increase significantly in CON, but not in DCA-treated subjects. PGC1α mRNA expression has previously been shown to increase during starvation [24], and with weight loss [25]. DCA may have had the effect of blocking any fasting-induced increase in PGC1α mRNA, through increasing carbohydrate utilisation, preventing the cell from sensing a physiological negative energy balance normally associated with saline infusions following an overnight fast.…”
Section: Discussionmentioning
confidence: 99%